CoAP conformance testing based on TTCN-3 - Hong-qing DU; Xiao-hong HUANG; Jia-jie He (Tongxin xuebao)
Protocol conformance test is of great importance in making sure that the protocol implementations conform to the protocol specification,thus helps protocol implementer to improve the implementations.CoAP (constrained application protocol) is a generic Web application specified for constrained nodes and constrained network which is currently an Internet draft.A CoAP conformance test suite based on TTCN-3,a standardized testing language,was designed,implemented and used after analyzing the protocol.